2005
DOI: 10.1002/ijc.21205
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone induces apoptosis through activation of caspase‐8 and mitochondrial events in p53‐null myeloblastic leukemia HL‐60 cells

Abstract: Thymoquinone (TQ), the major biologically active component isolated from a traditional medicinal herb, Nigella sativa Linn, is a potential chemopreventive and chemotherapeutic compound. Despite the promising antineoplastic activities of TQ, the molecular mechanism of its pharmacologic effects is poorly understood. Here, we report that TQ exhibits antiproliferative effect, induces apoptosis, disrupts mitochondrial membrane potential and triggers the activation of caspases 8, 9 and 3 in myeloblastic leukemia HL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
166
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(182 citation statements)
references
References 37 publications
14
166
1
1
Order By: Relevance
“…Thymoquinone (TQ), the most abundant component of black seed oil, has been reported to exhibit antioxidant (4)(5)(6), antiinflammatory, and chemopreventive (7-9) effects. For instance, TQ has been shown to suppress the proliferation of various tumor cells, including colorectal carcinoma, breast adenocarcinoma, osteosarcoma, ovarian carcinoma, myeloblastic leukemia, and pancreatic carcinoma (7,(10)(11)(12)(13)(14), although it is minimally toxic to normal cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…Thymoquinone (TQ), the most abundant component of black seed oil, has been reported to exhibit antioxidant (4)(5)(6), antiinflammatory, and chemopreventive (7-9) effects. For instance, TQ has been shown to suppress the proliferation of various tumor cells, including colorectal carcinoma, breast adenocarcinoma, osteosarcoma, ovarian carcinoma, myeloblastic leukemia, and pancreatic carcinoma (7,(10)(11)(12)(13)(14), although it is minimally toxic to normal cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…Cell proliferation (Fig. 1A) and cell viability ( A c c e p t e d M a n u s c r i p t respond to TQ within 24h and at the previously published concentrations [24][25][26][27][28].…”
Section: Tq Inhibits Cell Growth and Induces Cell Cycle Arrest Of Jurmentioning
confidence: 70%
“…It has been suggested that TQ, as a DNA damaging agent, is a potential reactive oxygen species (ROS) producer which exerts its anti-cancer effects by inhibiting cell growth, arresting cell cycle progression and inducing subsequently apoptosis [23][24][25][26][27][28][29]. p53-dependent [26] and p53-independent pathways [23,27] have been evidenced to explain the cellular actions of TQ. In HCT-116 colorectal cancer cells, TQ-induced apoptosis involves an upregulation of both p53 and p21 WAF1/CIP1 expressions, concomitantly with a downregulation of the expression of the anti-apoptotic protein Bcl-2 [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…cancer diseases, including cervical cancer (Effenberger et al, 2010), blood cancer (El-Mahdy et al, 2005), hepatic cancer (Thabrew et al, 2005), colon cancer (Salim and Fukushima, 2003), pancreatic cancer (Chehl et al, 2009), skin cancer (Salomi et al, 1991), fibrosarcoma (Awad, 2005), renal cancer (Khan and Sultana, 2005), prostate cancer (Yi et al, 2008), and breast cancers (Farah and Begum, 2003;Ahmad et al, 2012). Pharmacologically important components of N sativa extracts have also been studied against lung cancer as an anticancer agent.…”
Section: Introductionmentioning
confidence: 99%